Предмет: Алгебра,
автор: nadik2
(2х-1)*(2х+1)-(2х+3)^2=38 помогите
Ответы
Автор ответа:
0
( 2x - 1) * ( 2x + 1) - ( 2x + 3)^2 = 38
4
- 1 - 4
- 12x - 9 = 38
-1 - 12x - 9 = 38
-12x = 48 | : (-12)
X = -4
4
-1 - 12x - 9 = 38
-12x = 48 | : (-12)
X = -4
Автор ответа:
0
(2х-1)*(2х+1)-(2х+3)²=38
4х²-1-4х²-12х-9=38
-10-12х=38
-12х=38+10
-12х=48
х=-4
4х²-1-4х²-12х-9=38
-10-12х=38
-12х=38+10
-12х=48
х=-4
Похожие вопросы
Предмет: История,
автор: asdfqwer38
Предмет: Литература,
автор: Аноним
Предмет: Русский язык,
автор: mamyrbekmerey41
Предмет: Алгебра,
автор: SilentscreamSs
Предмет: Биология,
автор: TheAnya15